Dicamba-Tolerant Volunteer Soybean, Palmer Amaranth, and Green Foxtail Control in Irrigated Field Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Dicamba-tolerant soybean control was best when Armezon (topramezone) or Armezon Pro (topramezone + dimethenamid) was applied POST with atrazine and glyphosate, and when Status (dicamba + diflufenzopyr), atrazine, and glyphosate were applied POST. These treatments, along with PRE treatments of Armezon Pro and atrazine, completely controlled soybean. Similarly, control of Palmer amaranth and green foxtail was generally best with Armezon Pro and atrazine applied PRE or any herbicide combination applied POST. Corn receiving PRE treatments yielded 41 to 120 bu/a more grain than the weedy checks, whereas corn treated POST yielded 117 to 145 bu/a more grain than the untreated corn.
Keywords: herbicide resistance